I-invest data on listed companies PSE, Philippines April 2000 - Medina, Noel; Villareal, Janet; Regalado, Roselyn Q. (i-Invest Data Pte., 2000)
A fact book which serves as an investment guide on Philippine listed companies presenting all needed information in assessing true stock value. The book includes a company classification of 13 sub-industries according to their core business, ranking tables where companies of the same sector are grouped together and ranked, sector industry charts for each industry sector, first call earnings estimates provided by First Call, Thomson Financial Services, company capsule which gives readers the company' s background, portfolio of products and services, competitors and customers, current projects and expansion plans, as well as a brief analysis of the current results of the group, share information, financial results company' s management and shareholders.